Reducing effects of rodent malaria on hepatic carcinogenesis induced by dietary aflatoxin B1 - Subhkij Angsubhakorn (2018)
The present study was undertaken to evaluate the effects of Plasmodium berghei infection on the development of liver tumors induced in male Buffalo rats by aflatoxin B 1 (AFBF). Intraperitoneal (i‐p.) injection of 10 6 parasitized red blood cells (pRBC) into the rat 12 days prior to administration of 2 ppm dietary AFB 1 for 10 weeks diminished hepatocellular carcinoma (HCC) induction compared to that observed in rats given AFB 1 alone at weeks 60–82. No animals in a control group developed HCC lesions, while only 1 of 22 rats treated With P. berghei alone developed a neoplastic nodule at week 82. These data suggest a reducing effect of P. berghei on the development of liver tumors induced by AFB 1 in male Buffalo rats. Copyright © 1988 Wiley‐Liss, Inc., A Wiley Company